Gold Mine Wastewater Induced Morpho-physiological Alteration of Four Biodiesel Producing Species - Hamim Hamim; Lutfiani Lutfiani; Deden Saprudin; Putri Nur Azizah Hutagalung; Hadisunarso Hadisunarso; Luluk Setyaningsih; Hirmas Fuady Putra (Bogor Agricultural University, Indonesia, 2021)
This experiment aimed to determine the adaptability of four biodiesel-producing plants to gold mine wastewater based on morpho-physiological properties. Four species namely jatropha (Jatropha curcas), castor bean (Ricinus communis), wild candlenut (Reutealis trisperma) and bead tree (Melia azedarach) were grown in water culture using Hoagland solution for 2 weeks and then treated with gold mining wastewater at 0% (control), 25%, 50%, and 75% (v/v) for 3 weeks. Growth, anatomical and physiological characteristics were observed during the treatment. The results showed that gold mine wastewater significantly decreased growth of the four species despite varied among the species. Wastewater had significant effect on leaves anatomy of Jatropha but not on others. It also significantly induced the increase of malondialdehyde (MDA) content in Jatropha and castor bean, but not in wild candlenut and bead-tree. Meanwhile, the treatment significantly decreased chlorophyll content of all species with the most in bead-tree plant, and leaves relative water content (RWC) particularly in castor bean and bead-tree plants. There was strong negative correlation between the increase of MDA content and the decrease of chlorophyll content and leaf RWC. Among the four species, wild candlenut (R. trisperma) was the most resistant to gold mine wastewater based on morphological and physiological properties.